A Model for Teaching Slot Inlet Theory for Ventilation of Animal Housing Structures - Chastain, John P.; Hunter F. Massey (Journal of Agricultural Systems, Technology, and Management, 2020)
A model ventilation system was designed and built to provide a way for students to learn ventilation inlet theory in a practical laboratory setting. The model was designed to provide an adjustable ceiling and wall slot inlet, several fans to vary the air velocity through the inlet, a manometer to measure the static pressure drop across the inlet, ports to allow students to measure inlet velocity using a hotwire anemometer, a thermistor probe to measure air temperature, and ports along the ceiling of the model to measure the variation of velocity with respect to distance from the ceiling inlet baffle. The model was used by students to collect velocity versus static pressure drop data across a wide range of opening widths. A sample data set and analysis was provided to demonstrate how students used inlet theory to empirically determine the discharge coefficient for an inlet. Results from six laboratory groups, three ceiling inlets and three wall inlets, indicated that the average discharge coefficient was 0.50 regardless of inlet orientation. These results agreed with the literature for a ceiling inlet (0.50) but differed from the published value of 0.80 for a wall inlet. The reason for the discrepancy with the published value for the wall inlet was not possible to determine. Data collected by one group showed that the normalized maximum jet velocity (Vmax/Vinlet) of the ceiling inlet decreased with respect to distance from the inlet in a curvilinear manner with an R2 of 0.937 as expected based on inlet theory.